2015
DOI: 10.1152/ajpregu.00333.2014
|View full text |Cite
|
Sign up to set email alerts
|

Guanylin activates Clsecretion into the lumen of seawater eel intestine via apical Clchannel under simulated in vivo conditions

Abstract: Guanylin (GN) action on seawater eel intestine was examined under simulated in vivo conditions, where isotonic luminal fluid has low NaCl and high MgSO4 (MgSO4 Ringer). In Ussing chamber, MgSO4 Ringer induced serosa-negative potential difference (PD) even after bumetanide treatment, which is due to the higher paracellular Na(+) permeability over Cl(-), as confirmed by the replacement by MgCl2 (no Cl(-) gradient) or Na2SO4 Ringer (no Na(+) gradient). Luminal GN reversed serosa-negative PD, probably by enhancing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(56 citation statements)
references
References 40 publications
1
54
1
Order By: Relevance
“…Considerable expression of cftr was reported in some teleost species (Marshall and Singer, 2002; Gregŏrio et al, 2013), and it was recently reported that eel RGN induced CFTR insertion into the apical membrane of toadfish enterocytes (Ruhr et al, 2018). However, mucosal DPC, which effectively abolished GN-induced Cl - secretion in the eel intestine (Ando and Takei, 2015), failed to inhibit GN-induced HCO 3 - secretion in the present study. Thus, it is unlikely that GN directly stimulates Cl - channel including CFTR for HCO 3 - secretion in the SW eel intestine.…”
Section: Discussioncontrasting
confidence: 76%
See 4 more Smart Citations
“…Considerable expression of cftr was reported in some teleost species (Marshall and Singer, 2002; Gregŏrio et al, 2013), and it was recently reported that eel RGN induced CFTR insertion into the apical membrane of toadfish enterocytes (Ruhr et al, 2018). However, mucosal DPC, which effectively abolished GN-induced Cl - secretion in the eel intestine (Ando and Takei, 2015), failed to inhibit GN-induced HCO 3 - secretion in the present study. Thus, it is unlikely that GN directly stimulates Cl - channel including CFTR for HCO 3 - secretion in the SW eel intestine.…”
Section: Discussioncontrasting
confidence: 76%
“…As a second candidate for the route of HCO 3 - secretion, we considered Cl - channels such as CFTR, since GN stimulates apical Cl - channel in the SW eel intestine (Ando and Takei, 2015) and HCO 3 - is known to pass through the Cl - channels (Rubenstein, 2018). Two CFTR genes exist in the eel, but the expression of the cftr s was low and decreased after SW transfer in the eel intestine (Ando et al 2014; Wong et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations